A randomized, double-blind study on efficacy and safety of sepranolone in premenstrual dysphoric disorder. (November 2021) - Bäckström, Torbjörn; Ekberg, Karin; Hirschberg, Angelica Lindén; Bixo, Marie; Epperson, C. Neill; Briggs, Paula; Panay, Nick; O'Brien, Shaughn
Abstract: Women with premenstrual dysphoric disorder ( PMDD) experience mood symptoms related to the increase in progesterone and the neuroactive steroid allopregnanolone. Our hypothesis is that allopregnanolone is the symptom provoking factor. The rationale for the present study was to treat PMDD patients with the GABAA receptor modulating steroid antagonist, sepranolone (isoallopregnanolone). Patients (n = 206) with PMDD from 12 European centers were randomized in a parallel double-blind study and treated with placebo, sepranolone 10 mg and 16 mg. Patients administered sepranolone subcutaneously every 48 h during the 14 premenstrual days of three consecutive menstrual cycles. After obtaining informed consent, the PMDD diagnosis was confirmed according to DSM-5 and verified with two menstrual cycles of daily symptom ratings using the Daily Record of Severity of Problems (DRSP) scale in an eDiary. Inclusion and exclusion criteria stipulated that the women should be essentially healthy, not pregnant, have no ongoing psychiatric disorder or take interfering medications, and have regular menstrual cycles. The study's primary endpoint was the Total symptom score (Sum21, the score for all 21 symptom questions in the DRSP). In the prespecified statistical analysis the average score of the 5 worst premenstrual days in treatment cycles 2 and 3 were subtracted from the corresponding average score in the two diagnostic cycles. The treatment effects were tested using analysis of variance in a hierarchal order starting with the combined active sepranolone treatments vs. placebo. The prespecified analysis of Sum21 showed a large treatment effect of all three treatments but no statistically significant difference to placebo. However, the ratings of distress showed a significant treatment effect of sepranolone compared to placebo (p = 0.037) and the ratings of impairment showed a trend to greater treatment effect of sepranolone compared to placebo. Many women with PMDD had symptoms during a longer period than the late luteal phase. It has previously been shown that 9 premenstrual days may be more representative for comparison of PMDD symptom periods than the 5 worst premenstrual days. A post hoc analysis was undertaken in the per protocol population investigating the treatment effect during 9 premenstrual days in the third treatment cycle. The Sum21 results of this analysis showed that the sepranolone 10 mg was significantly better than placebo (p = 0.008). Similar significant treatment effects were found for the impairment and distress scores. A significantly larger number of individuals experienced no or minimal symptoms (Sum21 <42 points) with the 10 mg sepranolone treatment compared to placebo (p = 0.020). The results indicate that there is an attenuating effect by sepranolone on symptoms, impairment, and distress in women with PMDD especially by the 10 mg dosage. Sepranolone was well tolerated, and no safety concerns were identified. Highlights: A randomized, double-blind study using a GABAA receptor modulating steroid antagonist, sepranolone (isoallopregnanolone). Sepranolone attenuates symptoms, impairment, and distress in women with PMDD especially by the 10 mg dosage. Sepranolone was well tolerated, and no safety concerns were identified.